Iran's relations with Bahrain, Oman, and the United Arab Emirates - Güney, Nurşin Ateşoğlu; Keynoush, Banafsheh; Korkmaz, Vişne (Iran’s Interregional Dynamics in the Near East, 2021)
Few regions in the world are as torn by conflicts as the Near East, in which Iran plays a central role. Opportunities to engage with Iran are abundant, ...
Keywords: Relations – Oman – Iran